Cloud Computing Adoption among Higher Education Institutions in Yemen: An Integrated Conceptual Framework - Saleh, Abdulnoor; Mohd Drus, Sulfeeza; Salbiah M. Shariff, Siti (International Journal of Engineering and Technology, 2018)
Researches in technology adoption among the Middle Eastern countries are more concentrated on e-government, e-commerce, and internet banking domains. Higher education institutions (HEIs) in these countries fall behind their Western counterparts due to the cutting edge technology adopted for research, teaching, and collaboration in the Western countries. One of the Middle Eastern countries, which is the focus of this research, Yemen, still adopt the conventional way of teaching in the HEIs, which could result in failures to accomplish the optimal desired educational performance. Higher education sector in Yemen faces a number of obstacles and challenges in delivering a good education to its entire population in terms of lack of reliable infrastructure; limited financial resources; lack of teaching staff and expertise; and lack of IT personnel to manage the existing restricted IT infrastructure. Cloud computing, a pool of computer-related resources and services, is seen as one of new technologies which can assist in improving educational delivery in Yemen. Thus, this study firstly, identified the factors that influence the cloud computing adoption in general. Then, it categorized these factors into four (4) domains, namely technological, organizational, environmental and individual domains; and lastly, validated the selected factors using semi-structured interview with IT experts. Based on the validation session with the IT experts, the factors were ranked based on their applicability and suitability in Yemeniâ€™s higher education environments and 13 factors were selected. These 13 factors are adopted from Technology Acceptance Model (TAM), Theory of Reasoned Action (TRA), Technology-Organization-Environment (TOE) framework and Diffusion of Innovation (DOI) theory. Then, a conceptual framework was developed using these 13 factors to identify the significant factors that influence cloud computing adoption in HEIs in Yemen. It is hoped by having a better understanding on the factors that influence cloud computing adoption in HEIs in Yemen, the responsible parties such as the government agencies, HEIs managements and staff will be more prepared to ensure successful adoption of cloud computing in their HEIs and ultimately help Yemen to improve its higher education delivery to its people.Â Â